Construction Safety Risk Education for Construction Supervisors and Contractors in Deli Serdang Regency - EL- Matury, Herlina Jamaluddin (INSTITUT KESEHATAN DELI HUSADA, 2024)
This article presents the results of a community service program aimed at providing education on construction safety risks to supervisors and service providers in Deli Serdang Regency. Given the high rate of workplace accidents in the construction sector, this program is designed to enhance understanding and awareness of the importance of occupational safety. The methods employed include training, interactive discussions, and direct outreach at project sites. eval_uation results indicate a significant improvement in participants' understanding of safety procedures and risk management. Additionally, participants also showed positive changes in their attitudes toward the implementation of safety practices on-site. This program is expected to contribute to the creation of a better safety culture in the construction industry in Deli Serdang Regency. Through continuous educational efforts, it is hoped that the rate of workplace accidents can be minimized, thereby creating a safer working environment for all workers in this sector.